High retention of 15N‐labeled nitrogen deposition in a nitrogen saturated old‐growth tropical forest. (14th May 2016) - Gurmesa, Geshere Abdisa; Lu, Xiankai; Gundersen, Per; Mao, Qinggong; Zhou, Kaijun; Fang, Yunting; Mo, Jiangming
Abstract: The effects of increased reactive nitrogen (N) deposition in forests depend largely on its fate in the ecosystems. However, our knowledge on the fates of deposited N in tropical forest ecosystems and its retention mechanisms is limited. Here, we report the results from the first whole ecosystem 15 N labeling experiment performed in a N‐rich old‐growth tropical forest in southern China. We added 15 N tracer monthly as 15 NH4 15 NO3 for 1 year to control plots and to N‐fertilized plots (N‐plots, receiving additions of 50 kg N ha −1 yr −1 for 10 years). Tracer recoveries in major ecosystem compartments were quantified 4 months after the last addition. Tracer recoveries in soil solution were monitored monthly to quantify leaching losses. Total tracer recovery in plant and soil (N retention) in the control plots was 72% and similar to those observed in temperate forests. The retention decreased to 52% in the N‐plots. Soil was the dominant sink, retaining 37% and 28% of the labeled N input in the control and N‐plots, respectively. Leaching below 20 cm was 50 kg N ha −1 yr −1 in the control plots and was close to the N input (51 kg N ha −1 yr −1 ), indicating N saturation of the top soil. Nitrogen addition increased N leaching to 73 kg N ha −1 yr −1 . However, of these only 7 and 23 kg N ha −1 yr −1 in the control and N‐plots, respectively, originated from the labeled N input. Our findings indicate that deposited N, like in temperate forests, is largely incorporated into plant and soil pools in the short term, although the forest is N‐saturated, but high cycling rates may later release the N for leaching and/or gaseous loss. Thus, N cycling rates rather than short‐term N retention represent the main difference between temperate forests and the studied tropical forest.